Exploring the influence of lecturers’ teaching on student’s entrepreneurial intentions at a South African TVET College - Malawu, N.; Waghid, Z. (South African Journal of Higher Education, 2024)
The purpose of this study was to ascertain the challenges faced by a group of TVET college students in establishing their own entrepreneurial ventures. It further aimed to explore how lecturers’ current pedagogical approaches were or were not cultivating the entrepreneurial intentions of these students. The study employed a qualitative approach informed by an interpretive design. The sample participants included five (n=5) lecturers employed to teach entrepreneurship and business management across different courses, and thirty students (n=30) at a TVET college. The Theory of Planned Behaviour served as a barometer to both guide and frame the interpretation of results. A combined student- and teacher-centered approach was found, according to the views of the participants, to have a positive impact on the development of the participating students’ entrepreneurial intentions. The findings also suggest that using real-life business challenges as part of pedagogy, has the potential to help TVET college students develop entrepreneurial intentions, together with the appropriate skills, values, and attitudes.